Corynebacterium diphteriae invasion-associated protein (DIP1281) is involved in cell surface organization, adhesion and internalization in epithelial cells - Ott, Lisa; Höller, Martina; Gerlach, Roman G.; Hensel, Michael; Rheinlaender, Johannes; Schäffer, Tilman; Burkovski, Andreas (BMC Microbiology, 2010)
Corynebacterium diphtheriae, the causative agent of diphtheria, is well-investigated in respect to toxin production, while little is known about C. diphtheriae factors crucial for colonization of the host. In this study, we investigated the function of surface-associated protein DIP1281, previously annotated as hypothetical invasion-associated protein. Microscopic inspection of DIP1281 mutant strains revealed an increased size of the single cells in combination with an altered less club-like shape and formation of chains of cells rather than the typical V-like division forms or palisades of growing C. diphtheriae cells. Cell viability was not impaired. Immuno-fluorescence microscopy, SDS-PAGE and 2-D PAGE of surface proteins revealed clear differences of wild-type and mutant protein patterns, which were verified by atomic force microscopy. DIP1281 mutant cells were not only altered in shape and surface structure but completely lack the ability to adhere to host cells and consequently invade these. Our data indicate that DIP1281 is predominantly involved in the organization of the outer surface protein layer rather than in the separation of the peptidoglycan cell wall of dividing bacteria. The adhesion- and invasion-negative phenotype of corresponding mutant strains is an effect of rearrangements of the outer surface. BACKGROUND RESULTS CONCLUSIONS
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.LAP.coryne

Evaluation of lamina cribrosa and peripapillary sclera stiffness in pseudoexfoliation and normal eyes by atomic force microscopy - Braunsmann, Christoph; Hammer, Christian M.; Rheinlaender, Johannes; Kruse, Friedrich; Schäffer, Tilman; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2012)
Pseudoexfoliation (PEX) syndrome is a systemic disorder of the elastic fiber system that can lead to PEX glaucoma. Elastotic alterations in the lamina cribrosa (LC) of PEX eyes suggested biomechanical implications predisposing to pressure-induced optic nerve damage. In this pilot study, the stiffness of LC and peripapillary sclera (ppSC) in eyes with and without PEX syndrome were analyzed by atomic force microscopy (AFM) nanoindentation.Unfixed cryosections (5-?m thick) were prepared from the optic nerve heads (ONH) of three donor eyes with PEX syndrome and three age-matched control eyes. AFM force mapping was performed in selected regions of the central, midperipheral, and peripheral LC and the ppSC using a spherical cantilever tip. To determine the local Young's modulus of elasticity (YME) as a measure of tissue stiffness, force curves were acquired and analyzed using the spherical Hertz model.For the LC, the median YME values calculated from single stiffness maps averaged 17.2 (±2.7) kPa in normal eyes and 10.1 (±1.4) kPa in PEX eyes, indicating a significant PEX-related decrease in stiffness by over 40% (P < 0.01). The corresponding YME values for the ppSC, which revealed a 9-fold higher tissue stiffness than in the LC, averaged 158.3 (±59.8) kPa for control and 85.8 (±16.9) kPa for PEX samples.AFM was proven suitable for determining the stiffness of ONH tissues, encouraging further large-scale analyses. The marked decrease in stiffness, implying an increased deformability of the ONH in PEX eyes, may reflect an inherent tissue weakness rendering these eyes more vulnerable to glaucomatous damage.
EVALuna2:21095

Nanoscale analyses of Corynebacterium diphtheriae pili by atomic force microscopy - Rheinlaender, Johannes; Gräbner, Anna; Ott, Lisa; Burkovski, Andreas; Schäffer, Tilman (European Biophysics Journal, 2012)

Strain-specific differences in pili formation and the interaction of Corynebacterium diphtheriae with host cells - Ott, Lisa; Höller, Martina; Rheinlaender, Johannes; Schäffer, Tilman; Hensel, Michael; Burkovski, Andreas (BMC Microbiology, 2010)
Background: Corynebacterium diphtheriae, the causative agent of diphtheria, is well-investigated in respect to toxin production, while little is known about C. diphtheriae factors crucial for colonization of the host. In this study, we investigated strain-specific differences in adhesion, invasion and intracellular survival and analyzed formation of pili in different isolates. Results: Adhesion of different C. diphtheriae strains to epithelial cells and invasion of these cells are not strictly coupled processes. Using ultrastructure analyses by atomic force microscopy, significant differences in macromolecular surface structures were found between the investigated C. diphtheriae strains in respect to number and length of pili. Interestingly, adhesion and pili formation are not coupled processes and also no correlation between invasion and pili formation was found. Using RNA hybridization and Western blotting experiments, strain-specific pili expression patterns were observed. None of the studied C. diphtheriae strains had a dramatic detrimental effect on host cell viability as indicated by measurements of transepithelial resistance of Detroit 562 cell monolayers and fluorescence microscopy, leading to the assumption that C. diphtheriae strains might use epithelial cells as an environmental niche supplying protection against antibodies and macrophages. Conclusions: The results obtained suggest that it is necessary to investigate various isolates on a molecular level to understand and to predict the colonization process of different C. diphtheriae strains. © 2010 Ott et al; licensee BioMed Central Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.LAP.strain